Moderating effect of religiosity on the relationship between technology readiness, trust and diffusion of e-commerce (B2C) in Sultanate of Oman - Ali, Basharat (2016)
Electronic commerce has tremendously revolutionized the global economic system. Notwithstanding it has been playing a catalytic role in strengthening economies of the developing states, many countries are lagging behind in practicing electronic commerce due to numerous factors including technology readiness and trust. This study aimed to investigate the nature of relationship that exists between technology readiness, trust and diffusion of electronic while focusing on the public sector higher education institutions of the Sultanate of Oman. Furthermore, the study indented to examine the moderating effect of religiosity on the relationship between technology readiness, trust and diffusion of e-commerce. A structured questionnaire representing dimensions related to technology readiness, trust, religiosity and diffusion of electronic commerce was duly designed. Data was collected using survey method, through the distribution of the structured questionnaires to the public sector higher education institutions of Oman. The Partial Lease Square - Structural Equation Modeling (PLS-SEM) was employed to test the hypotheses. The results indicated that technology readiness, trust and religiosity have positive effects on the diffusion of e-commerce. Additionally, the findings revealed that religiosity significantly and positively moderates the relationship between technology readiness, trust and the diffusion of electronic commerce. The results imply that all the stakeholders must call their attention to the core areas of e-commerce like technology readiness, trust and religiosity to ensure a brighter future in today’s fast moving and competitive environment. While contributing to the body of knowledge and highlighting the importance of technology readiness and trust in the diffusion process of electronic commerce, the study appropriately provides practical, managerial, educational and theological implications to the prospective consumers, governmental officials, policy- makers and the e-commerce global community. In terms of limitations, this study is confined to the impacts of technology readiness, trust and religiosity on the diffusion of (business to consumer) electronic commerce, and has targeted academicians from the public higher education institutions, as respondents. On the basis of this study, future research can be conducted in the perspective of developing countries other than the Sultanate of Oman. It would also be valuable to employ the framework in conducting comparative studies on the developing and the developed nations